2016
DOI: 10.1093/jrs/few012
|View full text |Cite
|
Sign up to set email alerts
|

Threatened or Threatening? How Ideology Shapes Asylum Seekers’ Immigration Policy Attitudes in Israel and Australia

Abstract: Can different political ideologies explain policy preferences regarding asylum seekers? We focus on attitudes regarding governmental policy towards out-group members and suggest that perceptions of threat help to shape these policy attitudes. Study 1 compared public opinion regarding asylum policy in Israel (N = 137) and Australia (N = 138), two countries with restrictive asylum policies and who host a large number of asylum seekers; Study 2, a longitudinal study, was conducted during two different time period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…The distinction made in the 1980s onwards between asylum seekers (persons arriving without prior authorization) and “Convention” refugees (those granted residency visas prior to arrival) further put to test the viability of existing international procedures. Australia implemented stringent policies of deterrence to asylum seekers, and other countries of Europe and North America instituted similar policies and practices…”
Section: Oscillations In Public Perceptions and National Policiesmentioning
confidence: 99%
“…The distinction made in the 1980s onwards between asylum seekers (persons arriving without prior authorization) and “Convention” refugees (those granted residency visas prior to arrival) further put to test the viability of existing international procedures. Australia implemented stringent policies of deterrence to asylum seekers, and other countries of Europe and North America instituted similar policies and practices…”
Section: Oscillations In Public Perceptions and National Policiesmentioning
confidence: 99%
“…In addition, they may have a different cultural identity, religious identity, and value system than members of the host community. The combination of these different potential sources of threat (whether real or imagined) can affect individuals' attitudes toward refugees (e.g., Esses et al, 2003) and their support for restrictive immigration policies (e.g., Canetti, Snider, Pedersen, & Hall, 2016). Indeed, researchers agree that perceptions of threat are one of the most important predictors of attitudes and prejudice toward immigrants and other outgroups (e.g., Murray & Marx, 2013;Riek, Mania, & Gaertner, 2006).…”
Section: The Role Of Perceived Threat and Competitionmentioning
confidence: 99%
“…To further understand levels of support for restrictive refugee policies, Canetti et al (2016) investigated the role that threat plays in the relation between political ideology and migration policy attitudes. Their results demonstrated that, compared to individuals who identify with the political left, individuals who describe their political stance as more right-wing perceive asylum seekers as more threatening, which leads them to support policies that exclude asylum seekers.…”
Section: The Role Of Perceived Threat and Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amid social or political upheavals, outgroups including immigrants in Europe (Lesińska, 2014), asylum seekers and refugees in Australia (Correa-Velez, Spaaij, & Upham, 2013;Suhnan, Pedersen, & Hartley, 2012), and ethnic minorities in the USA (Torres, Driscoll, & Voell, 2012) were regarded as outgroups who disrupted different aspects of society including security and local culture. There is also evidence showing heightened perceptions of threat toward outgroups during disruptive social/political situations, such as Arab Israelis in Israel (Canetti, Snider, Pedersen, & Hall, 2016), Australian, European, Hong Kong, and African immigrants in Britain (Ford, 2011), and Muslim populations in European countries (Hjerm & Nagayoshi, 2011).…”
Section: Protestors: Ingroup-outgroup and Threat Perceptionsmentioning
confidence: 99%